Prevalence of Trypanosoma Cruzi antibodies in blood donors from the Sao Paulo State, Brazil, between 2012 and 2014 - Slavov, Svetoslav Nanev; Otaguiri, Katia Kaori; Pinto, Mariana Tomazini; Valente, Vanderléia Bárbaro; Ubiali, Eugênia Maria Amorim; Covas, Dimas Tadeu; Kashima, Simone (The Journal of Infection in Developing Countries, 2017)
Introduction: American tripanosomiasis (Chagas disease), the second most neglected disease in the world, is caused by the protozoan parasite Trypanosoma cruzi. Though natural transmission by insect vectors has been controlled, there is significant risk of T. cruzi transmission by blood transfusion in non-endemic regions, generally due to immigration processes from endemic areas. Methodology: The objective of this study was to evaluate anti-T. cruzi seroprevalence in blood donors from the western part of São Paulo State, Brazil, by serologic and immunofluorescence confirmation tests for the period between 2012 and 2014. Currently, this region is regarded as a non-endemic area for Chagas disease. Results: The confirmed overall T. cruzi seroprevalence among blood donors was 0.10%, which can be considered low compared to other Brazilian regions. Nevertheless, the distribution of the anti-T. cruzi antibodies within the examined region was uneven, and some areas of significantly higher prevalence were observed. Conclusions: We could consider two tendencies in the prevalence of T. cruzi: (i) residual older undiagnosed cases from São Paulo State, and (ii) immigration from endemic Brazilian or South American regions. The discordance obtained for T. cruzi prevalence by serologic and immunofluorescence methods demonstrates that more specific routine diagnosis is needed to diminish the cost of the assays and the loss of blood supply once all seropositive blood bags are immediately discarded.